2023
DOI: 10.3389/fmed.2022.1085339
|View full text |Cite
|
Sign up to set email alerts
|

Trained immunity as a possible newcomer in autoinflammatory and autoimmune diseases pathophysiology

Abstract: Autoimmune disorders have been well characterized over the years and many pathways—but not all of them–have been found to explain their pathophysiology. Autoinflammatory disorders, on the other hand, are still hiding most of their molecular and cellular mechanisms. During the past few years, a newcomer has challenged the idea that only adaptive immunity could display memory response. Trained immunity is defined by innate immune responses that are faster and stronger to a second stimulus than to the first one, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 126 publications
0
4
0
Order By: Relevance
“…The severity of AIDs commonly parallels the severity of chronic infectious conditions ( 111 , 112 ), which provides persuasive evidence that chronic infections contribute to the perpetuation and acceleration of autoimmune responses. Low-affinity autoimmune lymphocytes can escape the process of clonal selection and clonal deletion ( 113 116 ), and the development of AIDs critically requires the engagement of environmental factors to disturb immune homeostasis and generate high-affinity autoimmune lymphocytes by somatic mutations in the antigen-binding region (affinity mutation) ( 117 119 ).…”
Section: Contribution Of Inflammatory Stressors To Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of AIDs commonly parallels the severity of chronic infectious conditions ( 111 , 112 ), which provides persuasive evidence that chronic infections contribute to the perpetuation and acceleration of autoimmune responses. Low-affinity autoimmune lymphocytes can escape the process of clonal selection and clonal deletion ( 113 116 ), and the development of AIDs critically requires the engagement of environmental factors to disturb immune homeostasis and generate high-affinity autoimmune lymphocytes by somatic mutations in the antigen-binding region (affinity mutation) ( 117 119 ).…”
Section: Contribution Of Inflammatory Stressors To Autoimmune Diseasesmentioning
confidence: 99%
“…High-affinity antibodies or emCTLs cross-react with epitopes of autoantigens in certain tissues (molecular mimicry) ( 120 123 ). After being trained in response to microbial infections, these autoreactive lymphocytes migrate to remote organs, exert an immunological attack, and induce tissue damage when recognizing cognate autoantigens ( 117 119 ). 2) When tissue is infected by pathogenic microbes, autoreactive lymphocytes in the inflamed niche can be activated and trained by antigen-presenting cells and autoantigens, which form high-affinity autoimmune B and T cells and exert an immunological attack on corresponding tissues (bystander activation) ( 124 126 ).…”
Section: Contribution Of Inflammatory Stressors To Autoimmune Diseasesmentioning
confidence: 99%
“…Initial stimulation of innate cells via pattern recognition receptors (PRRs) leads to metabolic, mitochondrial, and epigenetic alterations, providing the cells with a more rapid and robust immune response upon re-exposure. This “memory” is the defining feature of trained immunity [8 ▪ ,9 ▪▪ ,10 ▪ ].…”
Section: Two Important Pathways Involved In Autoinflammationmentioning
confidence: 99%
“…It has also been shown that β-glucan, a potential inducer of trained immunity, can block NLRP3 inflammasome [18]. Metabolic and epigenetic changes have also been identified in other monogenic SAIDs, such as FMF, mevalonate kinase deficiency (MKD), tumor necrosis factor receptor associated periodic syndrome (TRAPS), as well as in polygenic diseases such as chronic nonbacterial osteomyelitis and Behcet disease, highlighting an important role that trained immunity can play in the pathophysiology of SAID [9 ▪▪ ,13 ▪ ,19–21].…”
Section: Two Important Pathways Involved In Autoinflammationmentioning
confidence: 99%